A study of the pulley diameter of mechanical banana slicer - Febriyan Fadli; Saipul Bahri Daulay; Ainun Rohana (Universitas Sumatera Utara, 2013)
The manufacturing process of agricultural produce into food stuffs is interesting to be known. In fact many of agricultural crops become more economics after heaving additional process. One of the manufacturing process is slicing. The aim of this research was to test the distance of pulley diameter, conducted in Februari 2012 to March 2012 at the Laboratory of Agricultural Engineering, Faculty of Agriculture, North Sumatera University, Medan, by literature study, experiment, observation, and testing of the equipment. The parameters observed were effective capacity, percentage of material left on the equipment, percentage of material which is not grated. The results of the research showed that the pulley diameter had highly significant effect on capacity, percentage of material which is not grated and percentage of material left on the equipment. The best pulley diameter was 8 inch